Letter from Patrick McCartan to Mrs. Walsh about the cancellation of his holiday to the United States over a visa issue - McCartan, Patrick, 1878-1963 (1922)
McCartan also discusses how "McCullough" called him and wanted him to meet "Smiddy" who McCartan did not want to meet as he is sick of politics.
Typescript.
Keywords: McCartan, Patrick, -- 1878-1963 -- Correspondence; Maloney, William Joseph Marie Alois, -- b. 1881; McCullough, Denis, -- 1883-1968; Smiddy, Timothy Aloysis, -- 1875-1962; Ireland -- History -- 1922-